Attitude and Behavior Sexual among Adolescents in Yogyakarta - Rahmah, Rahmah; AAAN, Wahyudina; WW, Sari (IJNP (Indonesian Journal of Nursing Practices), 2017)
Yogyakarta as a tourism city given more impact on attitude and behavior sexuality among adolescents. Notion and ideas about sexuality much influenced by the Globally issued environment. This study is basically on the attitude and behavior about sexuality among adolescent. It is of public health importance to examine this topic to inform sex education, policymaking, prevention and intervention program. This study explored the characteristics of sexual attitudes, and high risk premarital sexual behaviors among 106 unmarried youth aged 15 to 17 years usedsexual behavior questionnareand adopted from BriefSexual Attitude Scaleto investigate sexual attitudes. The scale measures sexual attitudes on four dimensions, being permissiveness, birth control (sexual practices), communion (investment in relationship), and instrumentality (pleasure-orientation to relationship). This study shown to female prefer low being permissiveness and male prefer high birth control , communion, and instrumentality for aspect sexual attitude. The male shown to prefer high premarital sexual behavior than female. Adolescents still have high risk sexual behavior, so parent, school and government should arrange intervention program together toward sex education for adolescents.Â Â Â